2007
DOI: 10.5326/0430143
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Tetanus in 20 Dogs: 1988–2004

Abstract: The case records of 20 dogs that were treated for tetanus between 1988 and 2004 were reviewed. Young, large-breed dogs were most commonly affected. Twelve dogs had a likely source of infection identified. All dogs were treated with intravenous antibiotics and supportive care, such as muscle relaxants and sedation for muscle tremors and rigidity. Sixteen dogs received tetanus antitoxin. The mortality rate was 50%. Complete recovery in survivors required approximately 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
3
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 13 publications
7
45
3
15
Order By: Relevance
“…It is possible that prevention of elaboration of additional toxin with antimicrobials may play a more critical role. In one case series, there was no statistically significant difference in survival, severity or duration of signs between dogs receiving TAT and those not receiving it (Bandt and others 2007). In another case series, a relationship between timing of administration of TAT, clinical course and outcome was not identified (Burkitt and others 2007).…”
Section: Tetanus Antitoxinmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that prevention of elaboration of additional toxin with antimicrobials may play a more critical role. In one case series, there was no statistically significant difference in survival, severity or duration of signs between dogs receiving TAT and those not receiving it (Bandt and others 2007). In another case series, a relationship between timing of administration of TAT, clinical course and outcome was not identified (Burkitt and others 2007).…”
Section: Tetanus Antitoxinmentioning
confidence: 99%
“…Sources: Wilson and Steiner 2005, Adamantos and Boag 2007, Bandt and others 2007, Burkitt and others 2007, Sprott 2008, Rodrigo and others 2012)…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…12 Clinical signs can take up to 3 weeks from the onset of infection to be apparent, although most cases exhibit symptoms within 5 to 12 days. 3,12,13 The clinical signs initially can be localized or generalized, with the former more common in dogs and cats. Only a few cats with tetanus have been documented in the literature; most had predominantly localized clinical signs.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…8 Death ranged between 8% and 50% of dogs in three recent retrospective studies, and many of these dogs demonstrated concurrent autonomic signs. 3,12,13 It is possible to see an effect on the autonomic system evidenced by episodes of bradycardia and tachycardia, hypertension, marked vasoconstriction, and pyrexia. 12,14,15 A study of 38 dogs with tetanus revealed that 37% demonstrated abnormalities of blood pressure or rectal temperature, or both, consistent with autonomic disturbance.…”
Section: Clinical Presentationmentioning
confidence: 99%